النظام القانوني لتداول الأسهم في شركة المساهمة - - فـــايد شيماء . - - طــلاب زينب (المسيلة, 2022)
إن ما يميز شركة المساهمة على سائر الشركات الأخرى هو إمكانية طرح أسهمها للتداول داخل السوق المالية، فمبدأ حرية تداول الأسهم حق كفلته كافة التشريعات بما فيها التشريع الجزائري، وتختلف طرق تداول الأسهم في شركة المساهمة باختلاف الشكل الذي يتخذه السهم. ويعتبر مبدأ حرية تداول الأسهم في النظام العام لا يجوز التعدي عليه، ولكن قد يلحق هذا الحق بعد التقييد، مما يحد من حرية التداول لفترة محددة بالقانون أو طبقا لما يتوافق عليه المساهمين في النظام الأساسي لشركة المساهمة، في حين قد تظهر بعض المشاكل التي من شأنها عرقلة سير عملية التداول ترجع إلى المساهم في حد ذاته أو إلى ظروف خارجة عن إدارته. الكلمات المفتاحية:شركة المساهمة،الأسهم، تداول الأسهم،حرية تداول الأسهم. Summary : The distinction of the joint stock company over other companies is the possibility of placing its shares for trading within the financial market. the principle of free circulation of shares is guaranteed by all legislation including Algerian legislation. the methods of trading shares in the shareholding company vary by the different form of the share. The principle of free circulation, of shares is a public order that may not be infringed but this right may be subject to certain limitations limiting, the freedom to trade for a period specified by law or in accordance, with the shareholders consensus in the statute of the shareholder while some problems may arise that would impede the course of circulation, they are due to the shareholder itself or to circumstances beyond the shareholders control. Keywords:shareholding company, shares, stock trading, stock trading freedom.
Keywords: شركة المساهمة،الأسهم، تداول الأسهم،حرية تداول الأسهم